Diagnosis and Treatment of Chronic Lymphocytic Leukemia: Recommendations of the French CLL Study Group (FILO). Issue 5 (23rd October 2020) - Quinquenel, Anne; Aurran-Schleinitz, Thérèse; Clavert, Aline; Cymbalista, Florence; Dartigeas, Caroline; Davi, Frédéric; de Guibert, Sophie; Delmer, Alain; Dilhuydy, Marie-Sarah; Feugier, Pierre; Fornecker, Luc-Matthieu; Ghez, David; et al.
Abstract : Abstract: As a result of significant recent developments, the management of patients with chronic lymphocytic leukemia (CLL) is changing, and new therapeutic options will continue to emerge in the near future. The recommendations of the French Innovative Leukemia Organization (FILO-CLL) group presented here are intended to provide practical recommendations for physicians taking care of CLL patients, taking into account the availability of both biological tests and therapies in daily practice in France at the time of publication. This text details the documented information and guidelines on diagnosis, indications for treatment, infectious complications and therapeutic strategies in frontline and relapsed CLL as well as in particular conditions such as autoimmune cytopenia or Richter syndrome.